Cardinal John Tong: renewal within tradition in the Catholic Church in Hong Kong - Chu, Cindy Yik-yi (Christianity in modern China, 2024)
This is a biography of Cardinal John Tong of Hong Kong, which charts his experiences through the Second World War, his time as a seminarian in Macau, and his studies in Rome during the Second Vatican Council (1962-65), which represented a pivotal moment in modern Catholic Church history. Upon his return to Hong Kong, he became a prominent figure within the Church. His story provides a more critical insight into the development of the Church in Hong Kong and China. Since 1979, Cardinal Tong has made over one hundred visits to the mainland of China, thereby making a significant contribution to the development of the Church. This biography constitutes an invaluable historical record of the Church since 1979. The author has made effective use of the personal writings of Cardinal Tong, which have not been previously utilized and have not been included in any published materials until now. This book illuminates the pivotal role of Hong Kong, which has been largely overlooked in previous accounts. The history of the Chinese Catholic Church will undoubtedly require rewriting following the publication of this biography